STRATEGY ANALYSIS OF GOPLAY PROMOTION ACTIVITIES THROUGH INSTAGRAM @GOPLAYINDONESIA IN ENCOURAGING CREATIVE INDUSTRIES IN INDONESIA - Priskila Primaningrum Demmasapo; Muh Akbar; Alem Febri Sonni (Jurnal Scientia, 2023)
This study aims to (1) analyze the promotion strategy used by GoPlay Indonesia through @goplayindonesia, and (2) analyze promotional activities carried out by GoPlay Indonesia in encouraging creative industries in Indonesia. This research uses a qualitative approach. In this study, primary data was obtained directly from informants by conducting interviews with Edy Sulystio as CEO of GoPlay Indonesia, and Franky Kuncoro as one of the content creators with several achievements in events held by GoPlay. The data in this study were also obtained from live streaming carried out by GoPlay sourced from Sandy Colondam as Head of Content GoPlay and Martinus Faisal as Chief strategic officers GoPlay. Data collection techniques used interviews, observation of the GoPlay and Instagram applications GoPlay and activity documentation. Data analysis techniques are data collection, reduction, presentation and conclusion. The study results show that 1) GoPlay Indonesia's promotion strategy is in accordance with what Philip Kotler and Keller formulated: service promotion places more emphasis on building closeness and trust between the parties involved. Via instagram GoPlay consistently delivers various information about live creator content streaming and informing about events held by GoPlay for viewers. 2) Promotional activities carried out by GoPlay are making big events that involve several parties and can be enjoyed by the wider community, even those who are not viewers GoPlay though. This event shows that GoPlay supports content creators to continue working so that a live creative industry climate continues stream GoPlay. GoPlay encourages the creative industry in Indonesia and invites creators to create quality content and find their community.